PERTUMBUHAN DAN PRODUKSI PADI GOGO VARIETAS SITU BAGENDIT PADA JARAK TANAM YANG BERBEDA DAN PEMBERIAN KOMPOS JERAMI - Febriyanti Indah Siregar; Jonatan Ginting; T. Irmansyah T. Irmansyah (Jurnal Agroekoteknologi, 2013)
The Growth and Production of Upland Rice Varieties Situ Bagendit In Different Planting Distance and Giving Straw Compost.  The aimed of this research to study the growth and production of upland rice varieties Situ Bagendit in different spacing and giving of straw compost. The research was conducted in the field UPT BBI, Tanjung Selamat at an altitude ± 57 meters above sea level since March 2012 until July 2012 using Randomized Block Design (RBD) factorial with two factors, which are the spacing (20 x 20 cm, 20 x 25 cm , 20 x 30 cm) and straw compost (0, 25, 50, 75, 100 g / planting hole). The parameters measured were plant height, number of tillers, straw dry weight, root dry weight, number of panicle, percentage of empty grain, the amount of grain productive, productive grain weight, grain 1000 grain weight, and grain production per plot. The results showed that the treatment of different spacing significantly affect the number of tillers 4-8 weeks after planting and root dry weight. Straw compost treatment significantly affect the number of tillers 4 weeks after planting, the percentage of empty grain and grain production per plot. The interaction between the different spacing and giving straw compost significantly affect grain production per plot.   Keywords : upland rice varieties situ bagendit, distance different plant, compost straw